Pengembangan Pariwisata pada Kawasan Saoraja Pattojo - Andi Abidah; Muh. Idhil Maming; Andi Yusdy Dwiasta (Seminar Nasional LP2M UNM, 2022)
Abstract. The ke-datu-an of pattojo area is one of the areas that has historical value that can be developed into a cultural tourism area, where the area is a cultural heritage that has a character like the area of old cities in Java. In the area there is a private residential building datu pattoj0 (saoraja tanre, pattojo palace office or known as saouraja batu / kance), these two buildings have  colonial architecture shape at the time. Around the sauraja (palace) there are squares, schools, mosques built by the kedatuan of pattojo during the reign of pattojo XI. Meanwhile, the location of the market has turned into a residential area. This research is a qualitative research by conducting a field survey. Area spots that can become tourist spots are developed by creating regional linkages so that visitors can easily access them. Keywords: : Saoraja Pattojo, Linkage, Heritage Tourism